A pedagogy changer: Transdisciplinary faculty self-study - Anastasia P. Samaras (Perspectives in Education, 2014)
In this article, I examine pedagogical understandings as captured through documented critical incidents of a transdisciplinary faculty self-study group which was designed and grounded in notions   of sociocultural theory. I report from my lens as facilitatorparticipant-observer and from my work with eleven other participants in a threesemester research project in which we conducted individual self-studies of profesional practice as well as a meta-study of the collective. A diverse data set, which included exit interviews, mid-project and end-of-project exit slips, and individual narratives, served to triangulate and support themes of our exchanging of pedagogical activities, learning with critical friends, and re-imagining our pedagogies. The study suggests that, as universities work to improve student learning, they might consider providing creative studio spaces for self-study of professional practice so that faculty can exchange their talents in order to more deeply understand and experience pedagogical innovations.